Pembinaan Karakter Disiplin Siswa Madrasah Ibtidaiyah Berbasis Penguatan Spiritualitas - Zunidar, Zunidar; Norhidayah, Siti (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study aims to analyze the development of student discipline character based on strengthening spirituality at SD Al-Ittihadiyah Laut Dendang. The approach used is qualitative research with a phenomenological approach, which involves observation, interviews, and documentation studies as data collection techniques. The results showed that the various spirituality activities implemented at school, such as congregational prayer, dhikr, religious studies, and prayer together, significantly contribute to the formation of students' disciplinary character. These activities teach time discipline, responsibility, and respect for applicable rules. However, challenges faced in their implementation include differences in student motivation, inconsistency in implementation by teachers, and the diversity of student backgrounds. Nevertheless, the strengthening of spirituality at SD Al-Ittihadiyah Laut Dendang has proven to be effective in improving student discipline in various aspects of life. This research provides a new contribution by showing the importance of strengthening spirituality in disciplinary character education in elementary schools, which can be a reference for other schools in shaping student character holistically.